SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN VENDOR BAHAN BAKU STRATEGIS DENGAN METODE ANALYTICAL HIERARCHY PROSES (AHP) DAN TOPSIS: Decision Support System (DSS), Multi-Criteria Decision Making, (MCDM), Analytical Hierarchy Process (AHP), Technique for Order Preference by, Similarity to Ideal Solution (TOPSIS) - Muhammad Damas Fatih; Pariyadi, Pariyadi; Rachmawati, Aulia; Anzari, Yandi (JURNAL AKADEMIKA, 2025)
Vendor selection at PT. Manufaktur Digital Jaya is still prone to subjectivity and bias that focuses on price, which risks causing production bottlenecks and quality decline. This decision is a complex Multi-Criteria Decision Making (MCDM) problem and requires an objective and structured assessment. This research aims to design a Decision Support System (DSS) to determine the best vendor at PT. Manufaktur Digital Jaya, using a combination of the Analytical Hierarchy Process  (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The AHP analysis was validated using Expert Choice software and the TOPSIS calculations were performed with Microsoft Excel. The AHP method is used to determine the priority weights of the assessment criteria, while TOPSIS is used to rank the vendor alternatives based on their closeness to the ideal solution. Five main criteria were established, covering Product Quality (C1), Unit Price (C2), Delivery Accuracy (C3), Service Capacity (C4), and Reputation (C5). The results of the AHP analysis show that Product Quality (C1) and Service Capacity (C4) are the criteria with the highest weights, reflecting the company's strategic priority on quality and long-term support.